2018
DOI: 10.1021/acs.jpcc.8b06102
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Map for Destabilization of Pt-Skin Au Nanoparticles via Atomic Scale Rearrangements

Abstract: A commonly used strategy to enhance the mass activity of Pt-based catalysts involves the synthesis of Au nanoparticles (NPs) with a monolayer-thick Pt-skin layer. The synergistic effect of Au and Pt results in a higher catalytic activity and better Pt utilization. However, the stability of the Pt-skin layer is questionable as our recent equilibrium Monte Carlo simulations predict that eventually the surface Pt is replaced by Au. The role of Au during destabilization of Pt-skin in vacuum and solution is investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…However, it is clear from the relative intensity of the PtO and Au­(OH) 3 reduction peaks in the CV and from the CO stripping peak area that Pt surface exposure continues to drop. Previous studies on the thermal and electrochemical restructuring of AuPt and AuPd nanoparticles including partial alloys and core–shells have postulated mechanisms involving Au migration outward from the core. , A molecular dynamics study on Pt-skin Au core NPs has also shown a similar mechanism to the one that we propose here, involving thermally activated detachment of Au atoms and subsequent climbing on top of Pt islands, which results eventually in full encapsulation of Pt into the subsurface …”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…However, it is clear from the relative intensity of the PtO and Au­(OH) 3 reduction peaks in the CV and from the CO stripping peak area that Pt surface exposure continues to drop. Previous studies on the thermal and electrochemical restructuring of AuPt and AuPd nanoparticles including partial alloys and core–shells have postulated mechanisms involving Au migration outward from the core. , A molecular dynamics study on Pt-skin Au core NPs has also shown a similar mechanism to the one that we propose here, involving thermally activated detachment of Au atoms and subsequent climbing on top of Pt islands, which results eventually in full encapsulation of Pt into the subsurface …”
Section: Resultssupporting
confidence: 76%
“…20,43−46 A molecular dynamics study on Pt-skin Au core NPs has also shown a similar mechanism to the one that we propose here, involving thermally activated detachment of Au atoms and subsequent climbing on top of Pt islands, which results eventually in full encapsulation of Pt into the subsurface. 47 Intriguingly, the core−shell structures do not exhibit Pt leaching, a deactivation process that is responsible for a significant loss in activity in commercial Pt and Pt alloy fuel cell catalysts. 30,48−50 We hypothesize that Au atoms migrating out of the core suppress Pt dissolution from the surface both by reducing the area of electrochemically exposed Pt and by preferentially stabilizing low-coordinate Pt atoms in the shell.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…properties of the MNP itself 1,[15][16][17] Focusing on catalytic applications, the role of the MNP's and NA's surface is central. In this context, electronic structure calculations represent an established route to infer the structure-property relationships which rule the activity, selectivity, and stability of the catalyst [18][19][20][21] . A knowledge of robust structure-property relationships, and of the finite temperature probability of observing MNPs and NAs with a given architecture, in turn, allows to draw design rules, to predict the activity, and to forecast the ageing of a nanocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of defects and subsurface vacancies has been shown in fundamental studies of Pt-based catalysts [13]. Further protocols have focused on ensemble effects in Pt overlayer [14] using a kinetic-mapping technique.…”
Section: Introductionmentioning
confidence: 99%